Influential factors in the consumption of non-recommended foods among education undergraduate students - Vallejo, Natali Kennet Paca; Miranda, Percy Samuel Yabar; Mendizabal, Brenda Karen Salas; Betancur, Heber Nehemias Chui (O Mundo da Saúde, 2026)
This study addresses the concerning global problem of low physical activity among adolescents, which affects approximately 80% of this population and generates a substantial economic burden on public health systems. The aim was to assess how dietary habits, physical activity, and excessive internet use predict the consumption of non-recommended foods among undergraduate students from the Faculty of Education Sciences at the Universidad Nacional del Altiplano de Puno. Using a quantitative, non-experimental, and explanatory design, data were collected from 563 students through a validated questionnaire with a Cronbach’s alpha of 0.92. Data were analyzed using multiple linear regression and Pearson’s correlation, identifying three significant variables influencing the consumption of non recommended foods: eating behavior (β = −0.105; p < 0.001), internet use (β = 0.130; p < 0.05), and gender (β = 0.204; p < 0.001). These findings demonstrate that healthy dietary practices, the digital environment, and gender differences play a crucial role in eating behavior. In conclusion, the results suggest that, to promote healthy eating and reduce the consumption of non-recommended products, it is essential to develop comprehensive strategies that include improving dietary habits, regulating the time spent and content consumed on the internet, and considering gender differences, in order to optimize the effectiveness of interventions among the university population, thereby contributing to the prevention of diet-related diseases and the promotion of public health.